The congruent, the incongruent, and the unexpected: Event-related potentials unveil the processes involved in schematic encoding. (August 2019) - Höltje, Gerrit; Lubahn, Bente; Mecklinger, Axel
Abstract: Learning is most effective when new information can be related to a preexisting knowledge structure or schema. In the present study, event-related potentials (ERPs) were used to investigate the temporal dynamics of the processes by which activated schemata support the encoding of schema-congruent information. Participants learned category exemplar words that were either semantically congruent or incongruent with a preceding category cue phrase. Congruent words were composed of expected (high typicality, HT) and unexpected (low typicality, LT) category exemplars. On the next day, recognition memory for the exemplars and the category cues they were presented with was tested. Semantically related lures were used in order to ascertain that memory judgements were based on episodic memory for specific category exemplars. Generally, congruent (HT and LT) exemplars were remembered better than incongruent exemplars. ERPs recorded during the encoding of the exemplar words were compared for subsequently remembered and forgotten items. Subsequent memory effects (SME) emerged in the N400 time window at frontal electrodes and did not differ between congruent and incongruent exemplars. In the same epoch, an SME with a parietal distribution was specific for congruent exemplars, suggesting that activated schemata strengthened memory for congruent exemplars by supporting the encoding of item-specific details. Subsequently remembered LT exemplars were associated with a late frontal positivity that is assumed to reflect expectancy mismatch-related processing such as the contextual integration of an unexpected word by the suppression of strongly expected words. A correlation analysis revealed that the greater the involvement of the processes reflected by the frontal positivity, the lower the level of false positive memory responses in the test phase one day later. These results suggest that the contextual integration of schema-congruent but unexpected events involves a weakening of the representations of semantically related, but unstudied items in memory and by this benefits subsequent memory. Highlights: Subjects learned words that were congruent or incongruent with a semantic category. Early frontal subsequent memory effects (SME) occurred irrespective of congruency. Congruent words were associated with superior memory and a parietal SME. Congruent low typicality words elicited a late frontal positivity. The frontal positivity was correlated with the false alarm rate to related lures.